United Nations peace operations and human rights : normativity and compliance - Maus, Sylvia, 1982- (Legal aspects of international organization, 2020)
"In 'United Nations Peace Operations and Human Rights: Normativity and Compliance, Sylvia Maus offers a comprehensive account of the human rights obligations of United Nations peace operations with a dual focus on the applicability and the content of UN peace operations' human rights obligations. Selected case studies show a triad of human rights gaps: a protection gap, an accountability gap and a remedy gap. Going further than purely legal studies on the subject, Maus makes use of international relations theory and addresses considerations of reputation and legitimacy as reasons for (non-)compliance with human rights by the UN. Based on this interdisciplinary approach, she convincingly proposes ways for enhancing human rights compliance in UN peace operations." -- back cover